Protesting Human Life Amendment; Supporting Women's Right to Choice by State Building on Mariposa Mall - Watkins, Howard::::::::: (1981)
Protesters walking in large circle holding signs: Babs Eskin carrying sign "My family is for Choice."; Channel 24 Live Remote Unit van in background